Trade Structure and Growth Effects of Taxation in a Two-Country World - Daisuke Amano; Jun-ichi Itaya; Kazuo Mino (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper explores the long-run impacts of tax policy in a two-country model of endogenous growth with variable labor supply. We focus on international spillover effects of tax reforms under alternative trade structures. It is shown that if the instantaneous utility function of the representative family in each country is additively separable and if international capital mobility is absent, then a change in taxation in one country does not directly affect capital formation in the other country. Such a conclusion is fundamentally modified if international borrowing and lending are allowed. Due to free financial flows, a change in tax policy in one country directly diffuses to the growth performance of the other country, even though preference structures are assumed to be log-additive forms.
Keywords: F43; O41; 330; factor-income tax; consumption tax; equilibrium dynamics; two-country model; endogenous growth; variable labor supply